Durban-Rivertown The functional and landscape recovery of residual urban areas (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2018)
The UIA congress has been the chance to reflect and to analyse the relationship between academic architecture and the reality of our society. In fact, the exercise is strictly connected with the socio-economic development. For this reason, a thoughtful approach to these new special need forces to a wider reflection that could be investigated by different points of view.